Emotional intelligence and psychographic profiles of the potential first class students - Ishak, Noor Azniza; Lim, Khong Chiu; Abdul Rahim, Fauziah; Mahat, Nor Idayu; Hashim, Nor Laily; Abdul Mutalib, Ariffin; T. Jdaitawi, Malek (Canadian Center of Science and Education, 2013)
The study examined the correlation between emotional intelligence dimensions and psychographic attributes among Potential First Class students.The study also explored the differences between age and ethnicity factors on the level of psychographics attributes among 424 potential first class students (69 males and 355 females).The result showed significant relationship between emotional intelligence dimensions as well as significant correlation between psychographics attributes.Furthermore, significant relationship was found between emotional intelligence construct and psychographics attributes.In addition, the results showed that there were differences on the level of psychographics attributes based on the age and ethnicity factors.Lastly, the study recommended that emotional intelligence, and psychological constructs are important factors that could improve student success, especially for the university students.